Dinamika Politik di Dunia Islam (Studi Tentang Perilaku Politik Muawiyah kaitannya dengan Pembentukan Dinasti dalam Islam) - Soraya Rasyid (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2011)
Muawiyyah became one of Islam rulers muchly determined by his capability and supporting moments. He was a smart politician who was able to manage military and political strategy. Beside that, the crucial moment at that time enabled him to take over the reign. Not only did he politically win the arbitrase (reconciliation between Muawiyah and Ali that was mediated by Amr bin Ash and Abu Musa al-As’ari), but also due to the death of Ali. The taking over of reign because of; 1) internal competition among Abdul Manaf descendents. Bani Umayah was a charismatic tribe in Mecca, but, due to Muhammad’s figure, Bani Hasyim had good position in Mecca taking place the position of Bani Umayyah; 2) the murder of Usman became political issue to decrease Ali’s charism. Through this moment, Muawiyah built a dynasty by modifying the governance system from khilafah to monarch.